Transcriptional Dysregulation and Post-translational Modifications in Polyglutamine Diseases: From Pathogenesis to Potential Therapeutic Strategies - Xiang, Chunchen; Zhang, Shun; Dong, Xiaoyu; Ma, Shuang; Cong, Shuyan (Frontiers in Molecular Neuroscience, 2018)
Polyglutamine (polyQ) diseases are hereditary neurodegenerative disorders caused by an abnormal expansion of a trinucleotide CAG repeat in the coding region of their respective associated genes. PolyQ diseases mainly display progressive degeneration of the brain and spinal cord. Nine polyQ diseases are known, including Huntington’s disease (HD), spinal and bulbar muscular atrophy (SBMA), dentatorubral-pallidoluysian atrophy (DRPLA) and six forms of spinocerebellar ataxia (SCA). HD is the best characterized polyQ disease. Many studies have reported that transcriptional dysregulation and post-translational disruptions, which may interact with each other, are central features of polyQ diseases. Post-translational modifications, such as the acetylation of histones, are closely associated with the regulation of the transcriptional activity. A number of groups have studied the interactions between the polyQ proteins and transcription factors. Pharmacological drugs or genetic manipulations aimed at correcting the dysregulation have been confirmed to be effective in the treatment of polyQ diseases in many animal and cellular models. For example, histone deaceylase inhibitors have been demonstrated to have beneficial effects in cases of HD, SBMA, DRPLA, and SCA3. In this review, we describe the transcriptional and post-translational dysregulation in polyQ diseases with special focus on HD, and we summarize and comment on potential treatment approaches targeting disruption of transcription and post-translation processes in these diseases.